The High Five Model as a predictor of academic performance over conventional psychological predictors in university students - Quito-Calle, Jessica V.; Cosentino, Alejandro César (Frontiers in Psychology, 2024)
The High Five Model (HFM) enables the identification of positive human characteristics based on an inductive psycholexic approach, encompassing positive human factors known as the "high factors": erudition, peace, joviality, honesty, and tenacity. The HFM is linked with elements of academic context and academic performance, utilizing self-reported values by students for performance analysis. This study aim was to demonstrate that HFM are predictors of university students' academic performance, beyond the predictive capacity of common predictors, such as academic motivation, exam anxiety, and academic procrastination. A quantitative methodology was employed for this purpose, involving a non-experimental cross-sectional correlational study using a non-probabilistic convenience sample. Study included 1007 Ecuadorian university students (n = 403 females) to verify the model through linear regression analysis. Findings indicate that the high factors of the HFM predict academic performance beyond the usual psychological predictors.